Analisisi Penelitian Performansi Pompa Air Pada Divisi Persemaian Di Kalimantan Timur - Ferdnian, Marsius; Joni Pasau, Fransye (Indonesian Society of Applied Science, 2025)
The engine pump is used to move fluids by converting mechanical energy into fluid energy and pressure, then transporting the fluid through the piping system. The use of pumps to meet clean water needs. The method with the working principle or how the pump flows fluids or provides fluid power, the results of the study show that the pump capacity with a water discharge of 15 L / m, the total head is 4.807 m, and after knowing the curve where there is an increase in pressure at the outlet (discharge pressure) there will be a decrease in the amount of flow and the higher the amount of flow that comes out, the higher the pressure capacity of the fluid. In the demin water transfer pump, it is known that the available NPSH (6.7 meters) is greater than the required NPSH (6.2 meters), so the pump can. So to fill the water reservoir at the Permanent Nursery Service, the pump operates for 8.5 hours per day. Data analysis and discussion can be concluded that the pump capacity with a water discharge of 15 L/m, the total head is 4.807 m, In the demin water transfer pump it is known that the available NPSH (6.7 meters) is greater than the required NPSH (6.2 meters), so the pump can work without experiencing cavitation. So to meet the needs of the water reservoir in the Permanent Nursery Division, the pump operates for 8-5 hours per day.